2017
DOI: 10.1097/pts.0000000000000444
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Dental Office–Originating Adverse Events: The Dental Practice Study Methods

Abstract: Background: Preventable medical errors in hospital settings are the third leading cause of deaths in the United States. However, less is known about harm that occurs in patients in outpatient settings, where the majority of care is delivered. We do not know the likelihood that a patient sitting in a dentist chair will experience harm. Additionally, we do not know if patients of certain race, age, sex, or socioeconomic status disproportionately experience iatrogenic harm. Methods:We initiated the Dental Practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…The quantification of adverse events may vary according to the disease or patient’s condition, the complexity of the procedures, and the professional’s knowledge and skills. A recent survey conducted in two US dental schools and one multispecialty large group practice listed the most common adverse events (and respective procedures) occurring in dentistry 6 : (a) an inability to swallow (dental anesthesia) 6 ; (b) severe tachycardia and light‐headedness and chronic trauma to tongue from margin of dental restoration (dental filling) 6 ; (c) persistent bleeding and involuntary trauma to soft tissue remote from the surgical site (dental extraction) 6 ; (d) persistent traumatic ulcer (use of a lower partial removable denture) 6 ; (e) development of wounds after a traumatic dental procedure and bone damage (dental implant surgery) 6 ; and (f) oral soft tissue laceration from loose wires (orthodontic procedure) 6 . However, the issue of whether the reporting of adverse effects or not is important, although straightforward and somehow obvious, deserves some additional insights.…”
Section: The Importance Of Reporting Errors and Complications In Clin...mentioning
confidence: 99%
See 2 more Smart Citations
“…The quantification of adverse events may vary according to the disease or patient’s condition, the complexity of the procedures, and the professional’s knowledge and skills. A recent survey conducted in two US dental schools and one multispecialty large group practice listed the most common adverse events (and respective procedures) occurring in dentistry 6 : (a) an inability to swallow (dental anesthesia) 6 ; (b) severe tachycardia and light‐headedness and chronic trauma to tongue from margin of dental restoration (dental filling) 6 ; (c) persistent bleeding and involuntary trauma to soft tissue remote from the surgical site (dental extraction) 6 ; (d) persistent traumatic ulcer (use of a lower partial removable denture) 6 ; (e) development of wounds after a traumatic dental procedure and bone damage (dental implant surgery) 6 ; and (f) oral soft tissue laceration from loose wires (orthodontic procedure) 6 . However, the issue of whether the reporting of adverse effects or not is important, although straightforward and somehow obvious, deserves some additional insights.…”
Section: The Importance Of Reporting Errors and Complications In Clin...mentioning
confidence: 99%
“…The quantification of adverse events may vary according to the disease or patient's condition, the complexity of the procedures, and the professional's knowledge and skills. A recent survey conducted in two US dental schools and one multispecialty large group practice listed the most common adverse events (and respective procedures) occurring in dentistry 6 : (a) an inability to swallow (dental anesthesia) 6 ; (b) severe tachycardia and light-headedness and chronic trauma to tongue from margin of dental restoration (dental filling) 6 ;…”
Section: The Imp Ortan Ce Of Rep Orting Error S and Compli C Ati On S...mentioning
confidence: 99%
See 1 more Smart Citation
“…1 Previous attempts have been made to define or categorise patient safety incidents specific to primary care dentistry. 8,9 A recent study by Black & Bowie 10 found that the following events may be considered as adverse or never events related to dentistry (listed in order of risk to patient):…”
Section: Patient Safety In Dentistrymentioning
confidence: 99%
“…While the first studies in patient safety aimed to measure the incidence or prevalence of AE to know the problem's magnitude 6 , the initial studies in Dentistry, besides measuring their frequency, aimed to understand their causes, sparking reflection on the inherent challenges in the specificities of dental practice. From the perspective of measuring the incidence/prevalence of harms, the studies 12,21,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43 produced findings that ranges from the complications of local anesthesia/sedation; lesions to the tongue and lips; and loss of teeth from switched tooth extractions, ocular lesions and even death. Incidents involved allergies, infections, diagnostic delay or failure, and failure in the procedure, among others.…”
Section: The Problem's Size and Understanding Its Causesmentioning
confidence: 99%